CD4 Count and Central Nervous System Infection among HIV/AIDS Patients in an Indonesian Presidential Hospital from 2020 to 2022 - Ramadina, Annisa Azzahra; Astari, Riezky Valentina; Yusmaini, Hany; Saleh, Arman Yurisaldi (Folia Medica Indonesiana, 2024)
Highlights: 1. There were insufficient data on the correlation between CD4 count and central nervous system infection as well as the risk magnitude of the infection for HIV/AIDS patients in Indonesia. 2. This study revealed a significant correlation between CD4 count and the incidence of central nervous system infection in HIV/AIDS patients, showing an increased risk with a low CD4 count. 3. The findings suggest that CD4 count is a vital parameter in determining therapy and evaluating the presence of opportunistic infections in HIV/AIDS patients. Abstract People living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), referred to as PLWHA, have a high rate of mortality and morbidity due to opportunistic central nervous system infections. The infections are attributed to the immune deficiency caused by HIV exposure to the immune system's cluster of differentiation 4 (CD4) cells. This allows the central nervous system, the most vital body system, to acquire an opportunistic infection. The purpose of this study was to determine the existence and magnitude of a risk by examining the correlation between CD4 count and the incidence of central nervous system infection among HIV/AIDS patients. This analytical cross-sectional study utilized a simple random sampling technique on the population of HIV/AIDS patients, which consisted of 80 medical records from January 2020 to December 2022. This study was conducted at Gatot Soebroto Presidential Hospital, also known as Gatot Soebroto Central Army Hospital, in Jakarta, Indonesia. The data analysis was performed using Fisher's exact test (p<0.05) and the prevalence odds ratio (POR). The results showed that 16.3% of the patients suffered a central nervous system infection, which consisted of cerebral toxoplasmosis (76.9%) and brain abscess (23.1%). The bivariate analysis suggested a significant correlation between CD4 count and the incidence of central nervous system infection, with an 11.5-fold increased risk for HIV/AIDS patients who had a CD4 count of <200 cells/mm3 (p=0.000; OR=11.5; 95% CI=2.9–43.8). This study concludes that CD4 count is correlated with the incidence of central nervous system infection, indicating a higher risk for HIV/AIDS patients with a low CD4 count.